Analisis Teknik Sinematografi Dan Color Grading Dalam Implementasi Melintasi Jejak Budaya Eksplorasi Di Daerah Kutai Kartanegara - Putri Qanitah Ramadhania; Agusdi Syahrizal; Damar Nucahyono (JURNAL VOKASI TEKNIK, 2024)
The short film "Crossing Cultural Traces" aims to understand how the younger generation, especially children and teenagers in Kutai Kartanegara, understand local culture through a short film entitled "Crossing Cultural Traces." This research emphasizes the role of children as introducers of culture, exploring the impact of short films on the young generation's interest in regional culture, as well as how this experience influences their identity. The use of cinematography and color grading techniques is a key element that supports the aesthetic representation of the message. This research uses the Multimedia Development Life Cycle (MDLC) method which allows the development of a systematic and effective cultural storyline. It is hoped that the research results will provide new insight into the role of children in preserving and introducing local culture in Kutai Kartanegara, as well as potentially contributing to similar development strategies in other regions in Indonesia.